PENGARUH ZAKAT DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP INCOME BANK UMUM SYARIAH DI INDONESIA PERIODE 2013-2018 - DAMRI BATUBARA (DIRHAM Jurnal Ekonomi Islam, 2021)
In theory, the increase in bank financial income should automatically increase its zakat. This is because income is no longer a measure of company performance, but instead zakat is a measure of the company's financial performance. However, the reality that occurs in the financial data of Islamic Commercial Banks in Indonesia for 2013-2018 does not always increase the bank's income, automatically its zakat also increases. Likewise with the theory of Corporate Social Responsibility (CSR), when the income of a bank company increases automatically, Corporate Social Responsibility (CSR) should also increase. However, in fact, in the financial data of Islamic Commercial Banks in Indonesia for 2013-2018, the increased bank income had no effect on the increase in their corporate social responsibility. This research is a quantitative research, the data source comes from secondary data in the form of time series and cross-section data from 2013-2018. The data analysis technique used panel data regression estimation method, with t test and f test. Which is analyzed using Eviews 9 Software. The results show that partially incame banking does not have a significant effect on zakat of Islamic Commercial Banks in Indonesia, partially corporate social responsibility has a significant effect on zakat of Islamic Commercial Banks in Indonesia. Meanwhile, simultaneously income banking and corporate social responsibility have a significant effect on zakat of Islamic Commercial Banks in Indonesia with a R2 value of 0.2092 or 20.92 percent, which means that 79.08 percent is influenced by other variables not discussed in this study.